Physico-chemical and grain cooking characteristics of selected rice cultivars grown in Morogoro - Shayo, N.B.; Mamiro, P.; Nyaruhucha, C. N. M.; Mamboleo , T. (Tanzania Journal of Science, 2021)
A study was carried out at Sokoine University of Agriculture to characterize the local rice varieties grown in Morogoro Region basing on their physical-chemical characteristics and cooking quality parameters. Five cultivars of rice were analyzed and these included Kaling'anaula, Kihogo Red, Salama M17, Supa and Salama. The samples were collected from Crop museum, SUA. The chemical analysis was done to determine the proximate composition, gelatinization temperature and gel consistency as main determinants of cooking quality, sensory evaluation tests was done as determinants for consumer acceptance. The proximate composition results indicated protein content values between 7.94 and 9.46%, ash content between 0.55 and 0.97%, fat content between 0.57 and 0.85%, fiber content between 0.29 to 0.73%. The amylose content values were between 18.25 and 19.25%. The gel consistency results showed that all cultivars analysed were hard with the gel length values between 27.50 and 31.80 mm There was a significant differences in composition as well as acceptability between the varieties. In all aspects, Supa cultivar appeared to be the most superior with mean score of 4.30 while Kihogo Red was the least superior with mean score of 2.93. The differences in the cultivars could be from environmental as well as genetic factors. This pauses a need for more studies to be directed to these factors in order to come up with useful alternatives on how to manipulate them so as to improve the cooking quality parameters, improve production of the local rice cultivars and increase the market demand for local rice.